Trim23 promotes WSSV replication though negative regulation of antimicrobial peptides expression in Macrobrachium nipponense. (August 2020) - Zhang, Ruidong; Dai, Xiaoling; Cao, Xueying; Zhang, Chao; Wang, Kaiqiang; Huang, Xin; Ren, Qian
Highlights: A novel Trim23 gene ( MnTrim23 ) was identified from M. nipponense, which belongs to C-IX family. MnTrim23 promotes the replication of WSSV and the expression of VP28 . MnTrim23 negatively regulates Relish mediated AMPs expression. AMPs inhibits the VP28 expression and WSSV replication. Abstract: The family of TRIM proteins with E3 ubiquitin ligase activity plays important roles in virus infection in vertebrates and invertebrates. In this study, a novel Trim gene shows high similarity to Trim23 (designated as MnTrim23 ) was identified from Macrobrachium nipponense . The MnTrim23 protein contains three conserved domains (one RING finger domain, two B-box, and one Coiled-coil region) at its N-terminal and one ARF domain at its C-terminal. The ARF domain characterizes the members of the Trim23 family. MnTrim23 belongs to C-IX family. Phylogenetic analysis shows that MnTrim23 has a closer genetic distance with other Trim23 proteins from invertebrates than that from vertebrates. MnTrim23 has higher expression level in the intestine and hepatopancreas than in the other immune tissues. The expression levels of MnTrim23 in the gills, stomach, and intestines are significantly up-regulated after white spot syndrome virus (WSSV) infection. Moreover, knockdown of MnTrim23 inhibits WSSV replication and VP28 expression, suggesting that MnTrim23 plays a positive role in WSSV infection. Further studies revealed that MnTrim23 negatively regulates the Relish transcription factor-mediated expression of antimicrobial peptides (AMPs). Synthetic AMPs inhibit VP28 expression and WSSV replication. These findings indicate that Trim23 promotes WSSV replication by inhibiting the expression of AMPs that are positively regulated by the host NF-κB signal pathway.